PENGARUH MODEL PEMBELAJARAN BERBASIS FENOMENA TERHADAP PEMAHAMAN KONSEP SISWA SMAN 1 KOPANG - Rahmiatul Akhir; Syifa’ul Gummah; Habibi Habibi (Lensa: Jurnal Kependidikan Fisika, 2015)
This research aimed to know there is or no effect of learning based phenomena model toward student’s conceptual understanding at SMAN 1 Kopang. The kind of this research was experimental research. Design of this research used Posttest Only Control Design with population was all of students at SMAN 1 Kopang. Sample of this research consist of two classes that is class X-1 asw control group and class X-2 as experimental group which used random sampling technique. Based on homogeneity and normality test showed that both of data was normal distribution. The data analysis used t-test. The result of t-test was 6,12 and t-table was 2,00, so Ha was accepted. The result of this research showed that there is effect of learning based phenomena model toward student’s conceptual understanding at SMAN 1 Kopang.